Extramedullary Hematopoiesis in the Uterine Cervix Associated with Tissue Repair. (11th September 2013) - Hanamornroongruang, Suchanan; Neungton, Chanon; Warnnissorn, Malee
Abstract : Extramedullary hematopoiesis (EMH) is the presence of hematopoietic precursors outside the bone marrow. This condition is usually associated with hematologic disorders. Although EMH can be found in almost every site in the body, female genital tract involvement is rare. The authors report EMH in the uterine cervix from a 64-year-old patient following cervical biopsy due to abnormal cervical cytology. Neither neoplasm nor hematologic disorder was detected before the diagnosis and after 1 year of follow up. To the best of our knowledge, this is the first reported case of EMH involving the uterine cervix which showed an association with tissue repair.